SIC FELICITER OMNIA: Titian’s ‘Allegory of Prudence’ reinterpreted - Markou, Georgios E. (My University, 2022)
“Provokingly enigmatic in respect of its iconographic context” was how Erwin Panofsky and Fritz Saxl described Titian’s Allegory of Prudence in their 1926 study of the painting. So began one of the most heated debates in the history of Venetian art: What is the meaning behind the tricephalous man and beast? Is it a representation of the three ages of man, an allegory of sin or a testament of the negotiations associated with the passing on of the painter’s property to his heirs? To complicate matters further, X-radiography has revealed that Titian’s original intention was different from the painting now in London’s National Gallery. The discovery of a visual source, which will be discussed in relation to the piece for the first time in this talk, might reveal what Titian considered the subject of his work to be. Moreover, unpublished documentary evidence, printed primary sources and extant artefacts imply whom the painter had originally in mind as the recipient.